If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = -7x + -5 Reorder the terms: 2 = -5 + -7x Solving 2 = -5 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 2 + 7x = -5 + -7x + 7x Combine like terms: -7x + 7x = 0 2 + 7x = -5 + 0 2 + 7x = -5 Add '-2' to each side of the equation. 2 + -2 + 7x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + 7x = -5 + -2 7x = -5 + -2 Combine like terms: -5 + -2 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| (3x^2)(-4x^3)(x)= | | (2a)(6ab)= | | 4r^2+40r+100=0 | | 9x+2=2x-5 | | 4m^2-36m+80=0 | | 3x+1y=353 | | (3.9xy^2)(-1.7xy^2)= | | 2x+3y=520 | | -7xy^3*-8x^4y^5z*-3x= | | 64p^2-25=0 | | 64p-25=0 | | x^2*x^3*3x^5= | | 9t^2+18t+1=0 | | 9t^2+18t+1=9 | | 4x^2-22x-26=0 | | 4.64/4 | | 13x+16=3x+20 | | -3+7x=6x | | 10x-3=5x+3 | | 10.8=x+3 | | .8= | | 7+7z-4=9z+19-4z | | 7/100+1/33 | | 2x^2+3x-2=x | | (5x-25)(7x+21)= | | (3x+24)(9x-54)= | | (x-8)(10x+50)= | | 1.2q-3.6-2.8q=-2.6q-1.8 | | (x+3)(2x+4)= | | 7y+9=8y+8 | | 2x+6-6=14-6 | | 5x^2+570x-36=0 |